Associations between the presence of bacteria and the physico-chemical parameters of water in peat swamp forest, paddy field and oil palm plantation in north Selangor, Malaysia - Aliu, Sule Hussein; Ismail, Ahmad; Azmai, Mohammad Noor Amal; Zulkifli, Syaizwan Zahmir; Mohd Roseli, Mohd Fauzul Aidil (Universiti Putra Malaysia Press, 2019)
This study determines the associations between the presence of bacteria and water physico-chemical parameters in peat swamp forest, paddy field and oil palm plantation in north Selangor, Malaysia. Sampling of bacteria and water physico-chemical parameters were conducted from four sites in the peat swamp forest, two sites each in paddy field and oil palm plantations. Oil palm plantation recorded the highest bacterial diversity (Shannon's H = 3.3713) and richness (IMargalef = 11.5955), while peat swamp forest showed highest bacterial evenness (Pielou's e = 0.9526). A total of 3,421 bacterial isolates from 39 bacterial species were obtained, which comprised of 11 Gram-positive and 28 Gram-negative bacteria. The highest number of bacteria was recorded in the oil palm plantation (1,552 isolates from 38 species), followed by the paddy field (1,191 isolates from 30 species) and the peat swamp forest (678 isolates from 22 species). In general, the most abundant bacteria was Escherichia coli (333 isolates; 9.73 %), followed by Salmonella spp. (288 isolates; 8.42 %), and Streptococcus agalactiae (252 isolates; 7.37 %). Moreover, E. coli recorded the highest isolated bacterium in the peat swamp forest (10.47%), paddy field (10.66%) and the oil palm plantation (8.7%). Inconsistent association was observed between the water physico-chemical parameters and the presence of bacteria in all studied habitats. However, multivariate analyses showed that water temperature, NH3-N, Cl2, DO, EC, SO4 and PO4 were able to influence the bacterial presence. This study showed that oil palm plantation and paddy field had the highest number of isolates, species, and bacterial concentrations due to the extensive anthropogenic activities in these areas.